Phosphorylation of deinococcal RecA affects its structural and functional dynamics implicated for its roles in radioresistance of Deinococcus radiodurans. Issue 1 (2nd January 2020) - Sharma, Dhirendra Kumar; Siddiqui, Mohammad Quadir; Gadewal, Nikhil; Choudhary, Rajan Kumar; Varma, Ashok Kumar; Misra, Hari Sharan; Rajpurohit, Yogendra Singh
Abstract: Deinococcus RecA (DrRecA) protein is a key repair enzyme and contributes to efficient DNA repair of Deinococcus radiodurans . Phosphorylation of DrRecA at Y77 (tyrosine 77) and T318 (threonine 318) residues modifies the structural and conformational switching that impart the efficiency and activity of DrRecA. Dynamics comparisons of DrRecA with its phosphorylated analogues support the idea that phosphorylation of Y77 and T318 sites could change the dynamics and conformation plasticity of DrRecA. Furthermore, docking studies showed that phosphorylation increases the binding preference of DrRecA towards dATP versus ATP and for double-strand DNA versus single-strand DNA. This work supporting the idea that phosphorylation can modulate the crucial functions of this protein and having good concordance with the experimental data. Abbreviations: DrRecA Deinococcus RecA DSB DNA double-strand breaks hDNA heteroduplex DNA STYPK serine/threonine/tyrosine protein kinase T318 threonine 318 Y77 tyrosine 77 Communicated by Ramaswamy H. Sarma